Ectopic gestation: a study illustrated by 25 cases - Fletcher, Hugh Nethersole (The University of Edinburgh, 1909)
In this thesis I propose, after reviewing the historical aspect of ectopie gestation, and discussing the etiology, to examine the mode of implantation and growth of the impregnated ovum, to follow its subsequent course and fate, with special reference to the anatomical positions and relations which it may assume, and to submit a classification.

I shall then go into the signs, symptoms and differential diagnosis of the various conditions, largely based on 25 cases.

I shall close my thesis with the history of these cases, and a brief commentary on each. I have personally observed and taken the histories of all of them and have assisted or been present at most of the operations.